Technological Cooperation Trends Under Conditions of the Modern World Economy - Anatol’evna Navrotskaia, Natalia; Alexandrovna Kovaleva, Ekaterina; Vyacheslavovna Zenkina, Elena; Muradovna Kutlyeva, Gozel’; Vyacheslavovna Bogacheva, Tatyana; Vital’evna Bondarchuk, Nataliya (International Journal of Engineering and Technology, 2018)
The authors emphasized key specific features of technological cooperation under conditions of the modern world economy and analyze modern trends of the world production ties development in high and medium technological economic sectors. They generalized main trends of technological cooperation development in the light of structural changes in the world economy, innovative production process and specific features of regional labor division.  It was concluded that structural changes in the world economy, an innovative production process and specific features of regional labor division formed a new location of the world production, an architecture and motivation of technological cooperation in the hi-tech and economic sectors. It was emphasized that an analysis of technological cooperation development for Russia should be performed with account of the mentioned world tendencies and special features of the national economy.